The Effects of Corporate Reputation on the Competitiveness of Malaysian Telecommunication Service Providers - Awang, Zainudin (2009)
The competition for customers among telecommunication firms in Malaysia is fierce. The competition among them is not only limited to new customers but also to the respective customer base. In this fiercely competitive environment, existing customers are frequently exposed to offers and counter offers from the competing firms. At the same time various persuasive messages being made to encourage customers to switch their service provider. Perhaps the corporate reputation of a firm could provide certain competitive edge which could ensure the growth and survival of a firm into the future amid the highly competitive environment. This study attempts to assess the influence of corporate reputation of the firms on their competitive advantage in the market from the customers’ perspective. The study sampled 600 individual customers who have been using the mobile service at a minimum of three years. The selected respondents have been experiencing the service provided by more than one telecommunication operators. The data were collected using self-administered questionnaires and analyzed using Structural Equation Modeling (SEM) in AMOS 6.0. The study found that the direct impact of firms’ corporate reputation on their competitive advantage in the market is not significant at